Implementasi Program Kerja Kampus Mengajar Dalam Media Pembelajaran Game Ular Tangga Guna Meningkatkan Keterlibatan Dan Pemahaman Numerasi Peserta Didik - firmasari, tamyiza; Permatasari, Galuh; hijrathaen, citra; Maysuroh, Siti (Jurnal Pengabdian Masyarakat Sains Indonesia, 2023)
The Teaching Campus Program is part of the MBKM program which provides opportunities for students to teach in schools and help improve students' literacy and numeracy. One of the implementations of this program is by using learning media in the form of snakes and ladders game. This game was conducted at SMPN 3 Terara to help improve students' understanding in literacy and numeracy. The game also trains learners' skills in cooperation, critical thinking, and refreshing their memory on previous materials. The Teaching Campus Program is a program that can improve the quality of education in Indonesia through learning media with snakes and ladders games. This program helps students solve problems in schools and is expected to continue helping schools in need. Many studies have been conducted to show the benefits of this program in improving students' literacy, numeracy, and technological adaptation. The purpose of implementing the Teaching Campus program is to empower students who collaborate with schools, through this teaching campus program, students have activities that are their responsibility in assisting learning activities, assisting technology adaptation, and assisting administration at the school where they are assigned during the teaching campus program.